Assessing the spillover effects of U.S. monetary policy normalization on Nigeria sovereign bond yield - Kpughur Moses Tule; Osana Jackson Odonye; Udoma Johnson Afangideh; Godday Uwawunkonye Ebuh; Elijah Abasifreke Paul Udoh; Augustine Ujunwa (Financial Innovation, 2019)
This study examines the spillover effects of U.S. monetary policy normalization on Nigeria 10-Year Treasury bond yield between 2011 and 2017, using the vector error correction model approach. Our results reveal that domestic factors, such as exchange rate and inflation, rather than the U.S. 10-Year sovereign bond yield, are the key drivers of Nigeria 10-Year bond yield. Additionally, the spillover effect from the U.S. monetary policy was amplified by oil price shocks and changes in Nigeria's monetary policy rates. Our counterfactual analysis confirms the findings.
Keywords: 650; Tapering; Nigeria 10-year sovereign bond yield; Error correction model; Counterfactual analysis